The influence of income level, home ownership, attitude, perceptions and experience on public preparedness for disasters across different age group in Penang - Chiew, Wan Yin; Khoh, Yi Xuan; Kong, Ming Jien; Lim, Zhi Xin; Teh, Sin Yee (2025)
This study explores how income level, homeownership, attitude, perceptions, and experiences affect disaster preparedness across age groups in Penang. With rising risks of floods, landslides, and earthquakes, it is vital to understand the socioeconomic and psychological factors shaping readiness. A total of 384 respondents from Generations X, Y, and Z were surveyed using a structured questionnaire within a quantitative framework. Factor analysis, reliability testing, correlation, and multiple regression were employed to assess the relationships between variables and preparedness. Results indicate that attitude and perception significantly enhance preparedness behaviors across all generations, highlighting the central role of psychological factors. Income level shows a small but significant positive effect, while homeownership exerts a positive yet non-significant influence. Conversely, prior disaster experience has a significant negative effect, suggesting that previous encounters may reduce rather than strengthen preparedness. These findings underscore the importance of integrating socioeconomic and psychological perspectives in disaster risk management. While financial and institutional factors contribute to readiness, attitudes and perceptions remain the strongest drivers. The study recommends age-specific preparedness programs, community training, and targeted awareness campaigns to address generational differences. Such strategies can strengthen resilience and promote a culture of preparedness in Penang. Keywords: Disaster Preparedness, Income Level, Home Ownership, Attitude, Perception, Past Experience, Age Groups, Penang Subject Area: HV551.2-639 Emergency management